ADVERSITY QUOTIENT DITINJAU DARI PSYCHOLOGICAL WELL BEING PADA ORANG TUA YANG MEMILIKI ANAK AUTISTIC SPECTRUM DISORDER (ASD) DI KOTA MEDAN - Fransiska Simorangkir; Elman Kristofan Ziliwu; Naomi Angel Theresia; Winida Marpaung (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2023)
The development of science and technology makes it easier for someone to access information, especially parents. It is easier for parents to detect growth and development problems in their children and to compare the growth and development of children of their age simply by seeking information that is not necessarily true. Nowadays, many parents realize that their children's growth and development are not the same as their children's age. One of them is the growth and development of children with Autistic Spectrum Disorder (ASD). Many families feel sad when they find out that their child has been diagnosed with autistic spectrum disorder, because the perception of their hopes and dreams for their child's future must be postponed. The purpose of this study was to test and determine the effect of Psychological well being and Adversity quotient. This study used a total sampling consisting of 51 parents who have autistic children in the city of Medan. Data were analyzed using pearson product moment correlation analysis. The results of this study indicate that there is a significant relationship between social support and psychological well-being in the Pearson Product Moment correlation coefficient = 0.454 and sig = 0.001 (p <0.005). This study shows that the effective contribution of psychological well being to adversity quotient is 20.6% and other unknown factors are 79.4%.